Conversational Implicature and Sarcasm in Football Mock Names Posted By @HaterCentral on X - Faraz Kahfi Djohari; Mahi M Hkikmat; Cipto Wardoyo (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines how sarcasm and conversational implicature are constructed in football mock names posted by @HaterCentral on X. Addressing a gap in previous studies that have not specifically explored the integration of sarcasm and implicature within mock naming practices, this research adopts a qualitative multimodal pragmatic approach. The data consist of 16 football mock names purposively selected from posts published between August 2025 and March 2026, based on their relevance to sarcasm and maxim flouting. The findings show that sarcasm is primarily realized through phonological wordplay, cultural references, and evaluative exaggeration, supported by visual elements and emojis. These expressions systematically involve the flouting of the Maxim of Manner and the Maxim of Quality, enabling indirect criticism through implicature. The study highlights that sarcasm in online discourse operates as a multimodal and structured communication strategy.